Metastatic cardiac tumors: literature review and own observation of testicular tumor metastasis in the right ventricle of the heart - Zakhartseva, L.M.; Zakharova, V.P.; Shatrova, K.M.; Chitaeva, G.E.; Vitovsky, R.M. (PH Akademperiodyka, 2018)
Summary. Background: Tumors of the heart are uncommon and usually benign (in 93% cases myxomas are observed). More often secondary, metastatic tumors are detected in the heart, as a rule, at pronounced progression of the malignant neoplasm with multiple lesions of other internal organs (lung, pleura, liver, etc.). Literature review on cardiac metastases of different tumors is given. Case Report: Own observation of a young man with rare single metastasis of malignant testicular germ cell tumor with predominance of embryonic carcinoma in the right ventricle of the heart is presented; the primary tumor was detected after metastasis revealing. The diagnostic algorithm using routine histological study supplemented with immunohistochemistry, including detection of cytokeratin pan, cytokeratin 5/6, cytokeratin 7, CD30, OCT4, TTF-1, hCG, and AFP markers expression, is described.